Enclave deliberation and social movement mobilization: the DDays in Occupy Central. - Yang, Shen (Social Movement Studies, 2020)
Scholars have called for a synergy between studies of deliberative democracy and social movements for their mutual enhancement. The existing literature generally applies the principle of deliberation to evaluate social movements, but few studies have examined the corresponding practice of deliberative democracy within a movement. The Occupy Central (OCLP) campaign in Hong Kong is a rare case in which the organizers incorporated Deliberation Days into a social movement; however, participant self-selection turned it into an instance of 'enclave deliberation'. This paper studies the impact of enclave deliberation on social movements based on the case of the OCLP campaign and argues that enclave deliberation can be a powerful tool for mobilization, particularly for gaining public support and for recruiting core participants. However, the coherence and support of the movement can decline when enclave deliberation is used to make decisions for the general public, because enclave deliberation incorporates only a small spectrum of like-minded participants who might not seriously engage with opposing views. The findings of this study imply that enclave deliberation could facilitate mobilization, but it has its inherent limitations for decision-making in a movement. Given the selective nature of social movements, deliberation within social movements is likely to be enclave deliberation in most cases. This study thus has significant implications for the practice of deliberation in social movements in other contexts.